Формування медіаграмотності майбутнього фахівця дошкільної освіти - Лисиця, Віталіна Вячеславівна; Конопля, Арсен Ігорович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The authors of theses outline the relevance of the issue of forming media literacy of future preschool education specialists; the interpretation of the key definition of scientific search - “media” is considered in the theses. According to the authors, it is possible to solve this issue by making additions to the EPP (educational and professional programs) in the specialty 012 Preschool Education: the introduction of academic disciplines, the purpose of which will involve the formation of competencies in future preschool education specialists, necessary for active and conscious participation in the life of the media society.